Determinants Of Risky Sexual Behaviours Among Adolescents In Secondary Schools In Rivers State: Implications For Counselling - Nwamadi, Love (Advances in Social Sciences Research Journal, 2021)
The study investigated determinants of risky sexual behaviours among adolescents in secondary schools in Rivers State. The study adopted the ex-post-facto research design. Four research questions as well as four corresponding hypotheses guided the study. The population of the study comprised 14,784 senior secondary school students (SSS 1, 2 and 3) in the 16 public secondary schools in Obio/Akpor LGA of Rivers State. A sample of 300 adolescents was randomly and independently selected using purposive sampling technique. Four instruments (questionnaire) were used to collect data for the study. They include; the Rosenberg Self-Esteem Scale (RSS), Risky Sexual Behaviours Scale (RSBS), Emotional Intelligence Scale (EIS) and Peer Group Influence Scale (PGIS). The instruments were designed on a four point Likert scale of Strongly Agree (SA) =4, Agree (A) =3, Disagree (D) =2, and Strongly Disagree (SD) =1. The Cronbach Alpha reliability was used to establish the internal consistency reliability coefficients of 0.81, 0.73, 0.67 and 0.71 respectively. Responses to the research questions were answered with mean and standard deviation, while the hypotheses were tested with z-test statistics. The findings of the study revealed that emotional intelligence and peer pressure were significant determinants of risky sexual behaviours among adolescents in secondary school in Rivers State, whereas self-esteem and gender are not. Based on the findings of the study it was recommended among others that counsellors should readily offer practical assistance to adolescents experiencing sexuality problems to enable them develop healthy sexual behaviours and maintain healthy relationships with others.